2015
DOI: 10.1016/j.jtcme.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Can naturopathy provide answers to the escalating health care costs in India?

Abstract: There are substantial areas of overlap between naturopathy and public health, which include a focus on health rather than disease, a preventive approach, and an emphasis on health promotion and health education. Public health can look to naturopathy for answers to the emergence of chronic disease through natural therapies, many of which can take the role of primordial and primary prevention of several diseases. Some selected naturopathic therapies include nutrition, hydrotherapy, fasting therapy, yoga, behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In a US review of the role of CAM under the Affordable Care Act, Thompson and Nichter [ 54 ] argue that CAM practitioners are well placed to provide cost-effective “preventive and promotive” health services. This argument is echoed (with specific reference to NM in India) by Tripathy [ 55 ], Kraft [ 32 ] Whilst these results are significant, research into N/HM in health promotion and prevention of disease is in its infancy. The Naturopathic Medical Research Agenda project [ 56 ] prioritises research into NM’s role in “… conditions with the highest burden of illness” and “…existing and emerging public health significance”, suggesting that funding and resources need to be directed towards health promotion and disease prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In a US review of the role of CAM under the Affordable Care Act, Thompson and Nichter [ 54 ] argue that CAM practitioners are well placed to provide cost-effective “preventive and promotive” health services. This argument is echoed (with specific reference to NM in India) by Tripathy [ 55 ], Kraft [ 32 ] Whilst these results are significant, research into N/HM in health promotion and prevention of disease is in its infancy. The Naturopathic Medical Research Agenda project [ 56 ] prioritises research into NM’s role in “… conditions with the highest burden of illness” and “…existing and emerging public health significance”, suggesting that funding and resources need to be directed towards health promotion and disease prevention.…”
Section: Discussionmentioning
confidence: 99%
“…We are of the view that public health can turn to Naturopathy as well for some answers in crisis such as COVID-19 [6]. We have also noted that both public health and Naturopathic principles are analogous [6] hence, policy makers can as well turn to Naturopathy for remedies to the escalating cases of public health issues [7] Though we found that there are challenges in the practice of Naturopathy from Stacy's narratives and the quantitative study (Fig. 20), we are of the view that these challenges stem partly from mistrust between Conventional and Naturopathic practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a clinical trial of naturopathy for primary cardiovascular disease prevention demonstrated effectiveness and cost-effectiveness, with a decisive contribution to cost savings being reductions in work place presenteeism (a confusing term, “presenteeism” is working while sick or with otherwise reduced physical and/or emotional function [93]), not the direct costs of the care provided [94]. Some authors have extended the potential of the value added by naturopathy to posit it has greater potential to reduce escalating costs in the developed and developing world due to its emphasis on prevention and patient self-management in the context of an escalating prevalence of non-communicable diseases [95].…”
Section: Disruptive Innovations Leverage New Values and Create Nementioning
confidence: 99%